HIWALAH SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA UTANG PIUTANG: Studi Kasus di BTM Mulia Babat Lamongan - Tohari, Chamim (Fakultas Syariah (Syari'ah Faculty ), 2024)
This study is motivated by the frequent occurrence of problems in financing contracts between customers and BTM Mulia Babat Lamongan, including unsustainable credit issues and defaults. As commonly believed, the emergence of a sharia-based economic system is expected to provide solutions to various economic challenges faced by the community. However, The existence of facts about the emergence of various problems in the implementation of hiwalah at BTM Mulia became the spark of the author's interest in conducting this research. This research aims to address the following questions: (1) What are the common issues arising from debt agreements at BTM Mulia? (2) How is the hiwalah contract implemented at BTM Mulia Babat as a solution to debt problems? (3) Does the implementation of the hiwalah contract at BTM Mulia Babat comply with Sharia Economic Law? This field research collects data directly from BTM Mulia and can be classified as empirical legal research. The study employs a descriptive qualitative approach with a deductive framework, focusing on the legal actions (tasarruf) involved in the implementation of hiwalah contracts at BTM Mulia. The findings of this study are as follows: Firstly, common problems in hiwalah implementation include customers failing to fulfill their contractual obligations, resulting in payment arrears or defaults. These issues stem from two main factors: the customer's economic condition and the customer's or debt collector's character. To address these problems, BTM Mulia follows these steps: (1) conducting regular billing, (2) issuing warning letters (SP 1, 2, and 3) if billing is ignored, (3) engaging in deliberation with the customer if there is no response, and (4) seeking resolution through the Religious Court if necessary. Secondly, BTM Mulia Babat implements hiwalah financing contracts in accordance with the terms and pillars outlined in Sharia Economic Law, specifically using the hiwalah bil ujroh contract. Thirdly, the implementation of hiwalah financing agreements at BTM Mulia Babat generally aligns with Sharia Economic Law, indicating that the institution's practices are largely compliant with sharia principles.